Analisis Pelaksanaan Program Pertemuan Peningkatan Kemampuan Keluarga (P2K2) dalam Mentransformasikan Pola Pikir dan Perilaku Ekonomi Keluarga Penerima Manfaat PKH melalui Pendekatan Bimbingan Konseling Islam di Desa Cisempur - Oktaviani, Eka Chandra; Miharja, Sugandi; Fajri, Suryadi; Hidayat, Taufiq (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2025)
The Family Hope Program (FHP) is a conditional social assistance initiative aimed at improving the welfare of underprivileged families, particularly through Family Capacity Enhancement Meetings (FCEM). In Cisempur Village, FCEM faces significant challenges in transforming the mindset and economic behavior of Beneficiary Families (BF). This study analyzes the implementation of FCEM in changing BF’s mindset and economic behavior, focusing on mentoring strategies through the Islamic Counseling Guidance (ICG) approach. The research uses a mini-ethnography method with participatory observation, in-depth interviews, and document analysis. The findings show that integrating ICG values, such as effort (ikhtiar), trust in God (tawakal), and social responsibility, enhances the spiritual awareness and economic skills of BF. However, sustaining the program’s impact remains a challenge, and it is recommended to develop educational methods based on Islamic values to reinforce long-term outcomes.